Exploring the Impact of Critical Reading on Academic Research Writing. The case of EFL Master 1 Students - TAYOUB Assia; GUERBAS Chahla (UNIVERSITÉ MOHAMED BOUDIAF - M’SILA, 2024)
This study is an attempt to explore the impact of critical reading on academic research writing. The main purpose is to assess the current level of critical reading skills among EFL Master's Level students and to examine the relationship between critical reading and academic research writing proficiency. The researchers have selected the descriptive mixed method as the most appropriate one. For this purpose, a students' questionnaire was addressed to Master One Linguistics students of the English Department at Msila University using a random sampling of 30 learners from the EFL 66 population. An email interview was also sent to the same sample. Similarly, a questionnaire was administered to 15 teachers in the field for further insights concerning the impact of critical reading on academic research writing. The findings showed that critical reading affected academic research writing in the sense of building a solid foundation for research, developing analytical skills, and enhancing comprehension and retention. Nevertheless, there are certain challenges that face both teachers and learners in practicing critical reading skills. For this purpose, some recommendations were presented to enable EFL learners to overcome these obstacles, and others were for teachers to improve the integration of critical reading into academic research writing instructions.
Keywords: impact; critical reading; academic research; writing